Technologies for enhancing pedagogy, engagement and empowerment in education creating learning-friendly environments - Le, Thao, 1948-; Lê, Quynh, 1962- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book explores how technology-based learning can enhance student engagement, performance, and empowerment, offering insights from educational programs, classroom teaching, and theory-into-practice research, and places educational technologies appropriately in their social and cultural contexts"--Provided by publisher.